2016
DOI: 10.1016/j.neuropharm.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine restores functional connectivity of the ventral attention network in schizophrenia

Abstract: While previous work has suggested that nicotine may transiently improve attention deficits in schizophrenia, the neuronal mechanisms are poorly understood. This study is the first to examine the effects of nicotine on connectivity within the ventral attention network (VAN) during a selective attention task in schizophrenia. Using a crossover design, 17 nonsmoking patients with schizophrenia and 20 age/gender-matched nonsmoking healthy controls performed a go/no-go task with environmental noise distractors duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
(85 reference statements)
1
8
0
Order By: Relevance
“…The VAN is the principle network associated with ‘bottom-up’ (stimulus-driven) attention processing, is modulated by shifts in attention, and may be a functional index of distractibility (Shulman et al, 2002, 2007). To examine the effects of nicotine on VAN connectivity in schizophrenia patients and controls, our group analyzed connectivity during the selective attention task described above (Smucny et al, 2016b). Using psychophysiological interaction-based modeling, we found that nicotine restored functional connectivity of the VAN during the task in schizophrenia.…”
Section: Neuroimaging the Cognitive Effects Of Nicotine In Schizophreniamentioning
confidence: 99%
“…The VAN is the principle network associated with ‘bottom-up’ (stimulus-driven) attention processing, is modulated by shifts in attention, and may be a functional index of distractibility (Shulman et al, 2002, 2007). To examine the effects of nicotine on VAN connectivity in schizophrenia patients and controls, our group analyzed connectivity during the selective attention task described above (Smucny et al, 2016b). Using psychophysiological interaction-based modeling, we found that nicotine restored functional connectivity of the VAN during the task in schizophrenia.…”
Section: Neuroimaging the Cognitive Effects Of Nicotine In Schizophreniamentioning
confidence: 99%
“…Evidence of this effect has been reported using fMRI (177182) and MEG (183). Future connectivity studies should incorporate these variables in their analyses.…”
Section: Challenges Pitfalls and Methodological Recommendations Formentioning
confidence: 87%
“…In particular, our findings of disrupted connectivity between the ventral attention network and dorsal attention network help elucidate the neural underpinnings of poor attentional control, a fundamental impairment in schizophrenia (e.g., (Nuechterlein et al, 2009)). Understanding the nature of network mechanisms underlying cognitive deficits of schizophrenia and how regional organization within and between networks is disrupted in terms of connectivity will aid in the development of novel therapeutic strategies (Hwang et al, 2010; Smucny et al, 2016a, 2016b, 2015) and may help shed light on the pathophysiology of this disorder.…”
Section: Discussionmentioning
confidence: 99%